Apigenin attenuates patulin-induced apoptosis in HEK293 cells by modulating ROS-mediated mitochondrial dysfunction and caspase signal pathway. (October 2017) - Zhong, Yujie; Jin, Chengni; Gan, Jing; Wang, Xiaorui; Shi, Zhenqiang; Xia, Xiaodong; Peng, Xiaoli
Abstract: Mycotoxins like patulin (PAT) are among the most significant food contaminant with regard to public health. This study aimed to evaluate the protective effect of apigenin (API), one of the most bioactive flavonoids in plant-derived food, on PAT-induced apoptosis in HEK293 cells. Cells were treated under basic conditions, 8 μM PAT without or with API (2.5, 5 and 10 μM) concomitantly for 10 h. API exerted renoprotective effect by inhibiting intracellular reactive oxygen species (ROS) accumulation, modulating oxidative phosphorylation especially elevating the expression of ATP synthase, re-establishing mitochondrial membrane potential (MMP) and maintaining higher intracellular ATP level, accompanied by p53, Bax downregulation and Bcl-2 upregulation. Thereby, cytochrome c release from mitochondria to cytoplasm was reduced, causing inhibition of initiator caspases-9 and executioner caspases (3, 6 and 7) expression and enzyme activities. Results revealed dietary apigenin attenuates patulin-induced apoptosis in HEK293 cells by modulating ROS-mediated mitochondrial dysfunction and caspase signal pathway. Highlights: Apigenin attenuate patulin-induced nephrocyte in vivo. ROS-mediated mitochondrial dysfunction regulation might be associated with the effect of apigenin. Apigenin inhibited the caspase cascade signal pathway.